(untitled) (Scientific journal of the Fergana State University, 2024)
This article presents an innovative and pedagogical model for improving the geological knowledge of future geography teachers in students. Also, the knowledge of future science teachers about the problems in the system of continuing education and scientific solutions to their elimination was analyzed. Future geography teachers can activate students in a way that does not satisfy their natural-geographical interests. This, of course, does not remain without the interest of Geographers-teachers today. Methodological training of the teacher it is necessary to regularly increase the skills of independent reading and learning, cognitivism and life experience during the life of the development of students ’ creativity abilities.